Dinamika Self-Compassion Pada Mahasiswa Baru Dalam Menjalani Pembelajaran Jarak Jauh (PJJ) Berbasis Aplikasi Zoom Atau Microsoft Teams - Crist Shella Sianturi, Margaretha Natalia; Irwansyah, Irwansyah (Jurnal Indonesia Sosial Sains, 2023)
During the Covid-19 pandemic, every university carried out a distance learning system or known as PJJ. Learning that was originally carried out in the classroom face-to-face must now be done online through applications such as zoom or microsoft teams. With the help of the application, teachers and students can still carry out the learning process. Self-compassion is key in app-based distance learning because not all individuals can adapt quickly to using an app. The purpose of this study is to find out how the dynamics or attitudes of new student self-compassion in undergoing PJJ based on the zoom application or Microsoft Teams. This research is qualitative using phenomenological study methods. The data collection technique was carried out by interviewing through Zoom meetings to five new students. The results showed that overall students have good self-compassion so that they do not interfere with the application-based online learning process. They can quickly adjust to changes and are able to operate every application used.